Quantitative evaluation of three soccer kicking techniques using full body 3D model - Gongbing, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: Soccer is a highly attractive sport with millions of spectators around the world. It has been reported to be the number one most watched and played sport worldwide. The basic idea of the game is one that never ceases to fascinate: goal. There exist various techniques for successfully gaining goals: maximal instep kick, bicycling kick and/or side volley. However, due to test constraints, difficulty in multidimensional signal exploration and the complexity of total body control, there is hardly any scientific study that describes theses techniques. The current study tried to address this deficiency by 1) providing 3D kinematic characteristics of these kicking techniques using a 15-segmental full body model, 2) comparing and contrasting the maximal instep, bicycling and side volley kicks and 3) exploring possible parameters for quantitative evaluations of kick quality. Methods The study involved the synchronization of 3 measuring systems - motion capture (VICON v8i, 12 cameras, 120 Hz, accuracy < 1.5 mm), video recorder, and sound capture - as well as biomechanical modelling. The VICON system tracked 42 reflective markers (12 mm) on the subjects` body and 3 on the soccer ball. The captured data was used to create 3D reconstructions of the movements and served as inputs to a 15-segment model in order to calculate range of motion of joints and other parameters. Video and sound capture permitted a traditional external view of motion analysis. To evaluate the kicks, 3 male groups of college team players (<26 yrs, over ten-years of experience) were tested. There were 12 subjects in the group of maximal instep kick, 6 in bicycle kick and 5 in side volley. The kicks were conducted on a 2 cm thick wrestling mat (to mimic the grass of a soccer field). An additional mat was used to reduce rebound of the kicked ball, preventing equipment damage. Each subject completed three good kicks using his dominant foot. Results / Discussion The 3D kinematics revealed the following features: For maximal instep kick: 1) a tension-arc was formed by three elements: kick side (KS) hip over-extension, knee flexion, trunk twist towards the non kick side (NKS), and abducted & over-extended NKS arm at the beginning of a kick. 2) The tensionarc released with a whip-like movement of the kick leg towards the ball, an upper body flexion and a trunk twist towards KS with the help of flexion and adduction of NKS arm. For bicycle kick: 1) Just before takeoff, NKS leg moved toward the athlete`s chest, as the trunk reached a horizontal position (Fig.2 middle). The instance angle between the two thighs would determine the kick power. 2) In airborne phase, the KS knee remained flexed during the downwards sweeping movement of NKS leg with extended knee. Simultaneously, KS leg moved upwards via flexion of KS hip. Because of the difference between the moments of inertia of flexed and extended legs, the flexion of KS hip was faster than the simultaneous extension of NKS hip. 3) Shortly before ball contact, an explosive extension of KS knee was observed, which formed a powerful whip-like movement of KS leg. For side volley: 1) Before the volley, athletes` trunk and hips rotated away from the goal. 2) During the takeoff, NKS leg was raised while the trunk and hip reversed rotational directions and came to twist toward the goal; at the same time, the trunk approached a more horizontal position (Fig.2 right). 3) While airborne, the kicking foot followed a smooth rainbow-like trajectory accompanied by continuous body rolling towards the goal. The results of this study reveal that the upper body movement contributes notably to soccer kicks, which was hardly revealed by previous studies. First, the tension-arc cannot be characterized without upper body kinematics. When advanced maximal instep kick is contrasted with novice kicks from previous study, it can be concluded that the tension-arc results in more efficient kicking. Secondly, larger angle between thighs at takeoff and whip-like movement of KS leg creates a more powerful bicycle kick. Thirdly, the twist of trunk and hip before takeoff and the following directionally-reversed body rolling during takeoff and airborne are keys for determining the quality of side volley. Lastly, timing is the most crucial element for bicycle kick and side volley. Conclusions Soccer kicks represent a full body, multi-joint coordination. 3D motion capture and full-body biomechanical modeling could help us extract the essence of kicking techniques for better understanding and coaching as well as improving kicks in practice.